Teenage parenthood of disabled girls and boys - Mach, Aleksandra (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The problem of disabled people’s marriage and parenthood, and which is essential, especially of those with intellectual disability, is more and more often discussed by the Polish researchers. The stereotypical perception of the disabled, mainly with an intellectual disability, by the general public, negating their adulthood, and at the same time a possibility of being a husband/a wife, a mother/a father is frequently emphasized in the literature on the subject. It is noted that difficulties in fulfilling parental functions of the aforementioned group may result not only from their heath condition, but also from their difficult economic situation, their lower skills to care for their offspring, loneliness or social isolation. In case of teenage adulthood there are other factors making the realization of maternal and paternal tasks difficult. Therefore, teenage parents with disability should be provided with versatile support in preparation for a responsible as well as satisfactory parenthood. The psychosocial functioning of disabled teenage parents appears to be an essential issue. Unfortunately, there are the situations of physical and emotional rejection of teenage parents not only by their peers but also their loved ones. Disabled girls who are pregnant are especially subject to stigmatization. The issues of teenage parenthood are a subject present in scientific literature, yet there are few studies in this field in the context of disabled girls’ and boys’ motherhood and fatherhood. Thus, the article presents the main research areas on teenage parenthood of the mentioned population using the example of foreign literature. Moreover, reference was made to Polish research which, as it was observed, generally does not refer to the indicated problematic aspects directly.
Keywords: teenage parenthood; disability; intellectual disability; disabled adolescents